Dynamic damage assessment of float glass under blast loading. Issue 11 (August 2019) - Zhou, Xiao-Qing; Wang, Ming-Yu; Li, Li-Xiao
Architectural glass, especially the float glass, is a fragile part of a building. The architectural glass becomes a large amount of high-speed flying debris under bomb attacks and accidental explosions, thereby causing serious threat to residents. This study investigates the dynamic responses of a normal float glass subjected to blast loading using the explicit dynamic finite element software LS-DYNA. A JH-2 material model, which considers the strain rate effect and damage accumulation, is adopted for the float glass. A preliminary study shows that the present numerical model combined with reasonable material parameters can simulate the failure mode of the glass and the ejection velocity of glass fragments after failure. The verified model is then used to investigate the dynamic damage responses of the float glass under different loading cases. The damage assessment criterion of float glass is established on the basis of the glazing protection levels defined by the General Services Administration of the United States. Comprehensive simulations are conducted on different amounts of explosive and standoff distances. The degrees of glass damage under different loading cases are determined by combining the projection velocity of glass fragments after failure with a kinematic equation. Finally, the damage assessment diagram of float glass under different amounts of explosive is presented and compared with those in FEMA 426.